Outdoor Learning through Scientific Excursions to Foster Exploratory Attitudes in Early Childhood - Ita Aristia Sa'ida (SAHABAT: Jurnal Pendidikan Anak Usia Dini, 2025)
This study explores the implementation of scientific excursions as a strategy to foster exploratory attitudes in early childhood education. Children at the early developmental stage naturally exhibit curiosity and a desire to explore their surroundings, making hands-on learning experiences essential. Scientific excursions provide opportunities for children to engage with real-life phenomena outside the classroom, allowing them to observe, question, and interact directly with their environment. This qualitative study employs a literature review approach, analyzing previous research and practical applications of outdoor educational activities and exploratory learning. Findings indicate that such excursions enhance cognitive, social, emotional, and motor development, while also promoting critical thinking and problem-solving skills. Teachers play a crucial role in facilitating these experiences, guiding learning while allowing children autonomy in exploration. The study highlights the importance of integrating experiential learning into early childhood education to cultivate lifelong curiosity and an active learning mindset. Implementing scientific excursions systematically can improve the quality and effectiveness of early childhood learning programs.